Konsep Kovenan dalam Perjanjian Lama: Analisis Kitab Pentateukh dari Perspektif Historis dan Teologis - Maxsi Tupamahu (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2025)
This study explores the concept of covenant in the Pentateuch through a qualitative-descriptive approach that integrates historical and theological analysis of God’s covenants with Noah, Abraham, and Israel at Sinai. Historical findings indicate that the covenantal structures in the Pentateuch correspond to treaty forms common in the Ancient Near East, particularly suzerainty treaties, yet the biblical covenants reveal a fundamental distinction by emphasizing God’s gracious initiative independent of political negotiations or human strategic interests. The theological examination affirms that the covenant is not merely a legalistic contract but a manifestation of God’s relational commitment that shapes the identity of His people as a covenant community grounded in divine faithfulness and promise. The Torah is understood as an expression of faith response arising from this covenantal relationship, rather than a prerequisite for salvation, thereby retaining its significance for the contemporary church as an ethical and spiritual framework guiding Christian praxis, character formation, and communal responsibility amid rapidly evolving social contexts. The integration of historical and theological perspectives demonstrates that the Pentateuchal covenant encompasses intertwined dynamics of grace, obligation, and identity formation, contributing theoretically to Old Testament studies, particularly covenant theology, while offering practical implications for ecclesial faith formation, the strengthening of communal spirituality, and ministry orientation rooted in a holistic understanding of the divine–human relationship. This research underscores the urgency of interpreting the Pentateuchal covenant through an interdisciplinary lens to meet the theological, ethical, and pastoral challenges faced by the church in the contemporary era.